2017
DOI: 10.3390/molecules22122106
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Partially Purified Lipases (ScLipA and ScLipB) from Schizophyllum commune UTARA1 Obtained via Solid State Fermentation and Their Applications

Abstract: Lipases with unique characteristics are of value in industrial applications, especially those targeting cost-effectiveness and less downstream processes. The aims of this research were to: (i) optimize the fermentation parameters via solid state fermentation (SSF); and (ii) study the performance in hydrolysis and esterification processes of the one-step partially purified Schizophyllum commune UTARA1 lipases. Lipase was produced by cultivating S. commune UTARA1 on sugarcane bagasse (SB) with used cooking oil (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Further, the purification process resulted in a reduction of sn‐2 MCFA content (from 38.70% to 29.35%) and an increase in sn‐2 LCFA content (from 61.30% to 70.65%), in which sn‐2 EPA reached 26.93%. Previous research has indicated that pancreatic lipase is a sn‐1,3‐specific lipase that acts on the sn‐1 or sn‐3 ester bond of the TAG molecule but with significantly lower specificity to EPA at the sn‐1,3 positions compared with other FAs 29,30 . The EPA‐enriched MLCT, where MCFA is predominantly located at the sn‐1,3 positions while EPA is mainly located at the sn‐2 position, could therefore be synthesized to promote absorption of EPA in cases of lipid malabsorption.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the purification process resulted in a reduction of sn‐2 MCFA content (from 38.70% to 29.35%) and an increase in sn‐2 LCFA content (from 61.30% to 70.65%), in which sn‐2 EPA reached 26.93%. Previous research has indicated that pancreatic lipase is a sn‐1,3‐specific lipase that acts on the sn‐1 or sn‐3 ester bond of the TAG molecule but with significantly lower specificity to EPA at the sn‐1,3 positions compared with other FAs 29,30 . The EPA‐enriched MLCT, where MCFA is predominantly located at the sn‐1,3 positions while EPA is mainly located at the sn‐2 position, could therefore be synthesized to promote absorption of EPA in cases of lipid malabsorption.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has indicated that pancreatic lipase is a sn-1,3-specific lipase that acts on the sn-1 or sn-3 ester bond of the TAG molecule but with significantly lower specificity to EPA at the sn-1,3 positions compared with other FAs. 29,30 The EPA-enriched MLCT, where MCFA is predominantly located at the sn-1,3 positions while EPA is mainly located at the sn-2 position, could therefore be synthesized to promote absorption of EPA in cases of lipid malabsorption. Clinical studies showed that the growth in body weight for cancer patients receiving chemotherapy significantly increased when EPA dosage was no less than 2 g d −1 .…”
Section: Changes In Fa Compositionmentioning
confidence: 99%
“…Fusobacterium nucleatum) (Fischer et al, 2012;Matsue et al, 2019). Lauric acid can be released after lipase digestion of trilaurin, a triglyceride that contains a significant amount of lauric acid (Kam, Woo, & Ong, 2017). However, the results showed that BTD did not significantly (p < 0.05) inhibit the growth of C. perfringens (Fig.…”
Section: Discussionmentioning
confidence: 96%